Formas de sacralizar a la figura real entre los mayas - Daniel Salazar Lama (Journal de la Société des Américanistes)
Classic Maya art reflects the ideology used by Maya rulers to exercise and legitimate their power over society. On sculptural supports, the rulers stand as the leading figure and the main axis structuring complex scenes and iconographic programs of public nature, where they are represented as sacred beings able to dominate the forces of nature and the cycles of life. The present study aims to identify the various iconographic traits as well as the concepts generated around the figure of the ruler in Lowlands’ architecture-integrated sculpture during the early Classic – a sculptural format that is one of the most elaborate expressions of glorification and exaltation of the Maya rulers.